Appendage‐patterning genes regulate male and female copulatory structures in horned beetles. Issue 4 (July 2015) - Macagno, Anna L.M.; Moczek, Armin P.
SUMMARY Explaining the extraordinarily rapid diversification of insect copulatory structures has been a longstanding objective in evolutionary biology. However, remarkably little is known about the developmental genetic underpinnings of their formation. Furthermore, recent work has questioned whether male genitalic structures in beetles are serially homologous to appendages, or even homologous to the genitalia of other orders. Using RNA interference, we demonstrate that several cardinal appendage‐patterning genes regulate the formation of copulatory structures in Onthophagus beetles of both sexes. These results are in strong disagreement with previous findings in the model beetle species Tribolium castaneum, but congruent with earlier studies in true bugs and flies. Our results support the hypotheses that genitalic development is largely conserved across insect orders, and that genitalia constitute serial appendage homologues. Moreover, we identify two patterning genes with striking phenotypic effects in both sexes. In these cases, the affected structures are known to interact functionally during copulation, but are not homologous to each other. This suggests that shared developmental regulation of male and female copulatory structures may extend beyond components related by descent to those related by function.